Corticospinal excitability, assessed through stimulus response curves, is phase-, task-, and muscle-dependent during arm cycling. (23rd January 2019) - Forman, Davis A.; Monks, Michael; Power, Kevin E.
Highlights: Corticospinal excitability to biceps brachii is phase-dependent during arm cycling. Corticospinal excitability to biceps brachii is task-dependent during arm cycling. Corticospinal excitability to the biceps and triceps brachii are different. Abstract: The purpose of the present study was to examine corticospinal excitability to the biceps and triceps brachii during arm cycling and an intensity-matched tonic contraction using stimulus response curves (SRCs) elicited via transcranial magnetic stimulation (TMS). Corticospinal excitability was assessed using TMS elicited motor-evoked potentials (MEPs) at eight different stimulation intensities (85–190% of MEP threshold). MEPs were recorded during arm cycling at two different positions, mid-elbow flexion (6 o'clock relative to a clock face) and mid-elbow extension (12 o'clock relative to a clock face), in addition to an intensity-matched (12 o'clock) tonic contraction. At the 12 o'clock position, the slope of the SRC was significantly lower during arm cycling than the tonic contraction for the biceps brachii (Cycling: 0.64 ± 0.47, Tonic: 1.02 ± 0.38, P < 0.05) but was not different for the triceps brachii (Cycling: 1.33 ± 0.49, Tonic: 1.48 ± 0.43, P = 0.42). Within arm cycling, the SRC slope was significantly greater at the 6 o'clock position than 12 o'clock position for the biceps brachii (6 o'clock: 1.37 ± 0.24, 12 o'clock: 0.64 ± 0.47, P < 0.05) but was not different for the triceps brachii (6 o'clock: 1.11 ± 0.28, 12 o'clock: 1.33 ± 0.49, P = 0.34). These findings demonstrate that corticospinal excitability to the biceps brachii is task-dependent during the extension phase of arm cycling. Neither position nor task influenced corticospinal excitability to the triceps brachii, providing further support that the motor control of locomotor outputs is muscle-specific.